Antibiotic Use in Very Low Birth Weight Neonates After an Antimicrobial Stewardship Program - Alberto Berardi; Isotta Zinani; Cecilia Rossi; Eugenio Spaggiari; Virginia D'Amico; Greta Toni; Luca Bedetti; Laura Lucaccioni; Lorenzo Iughetti; Licia Lugli (MDPI AG, 2021)
There is insufficient data regarding antimicrobial stewardship (AS) and outcomes of very low birth weight (VLBW) neonates after AS programs. This observational, retrospective study addressed AS and outcomes of VLBW neonates admitted to an Italian level-three center. Two periods were compared: (i) baseline, before AS (January 2011-December 2012) and (ii) intervention, after AS (January 2016-December 2017). Between these two periods, procedures were put in place to inform medical and nursing staff regarding AS. There were 111 and 119 VLBW neonates in the baseline (6744 live births) and in the intervention period (5902 live births), respectively. The number of infants exposed to antibiotics (70%) during the hospital stay did not change, but the total days of therapy (DOT, median 12 vs. 5) and DOT/1000 patient days (302 vs. 215) decreased in the intervention period (p < 0.01), as well as the median duration of first antibiotic treatment (144 vs. 48 h, p < 0.01). A re-analysis of single cases of culture-proven or culture-negative sepsis failed to demonstrate any association between deaths and a delay or insufficient antibiotic use in the intervention period. In conclusion, AS is feasible in preterm VLBW neonates and antibiotic use can be safely reduced.